Place and placelessness - Relph, E. (Pion, 2008)
First published over 30 years ago and still widely referenced even though out of print for some time, Edward Relph's Place and Placelessness has taken its place as a classic of the phenomenological approach to the study of place and has influenced a generation of scholars by its insights: insights presented with unusual clarity and precision. For this reprint Professor Relph has written a substantial new introduction setting his original text in its contemporary contest. He shows how the concepts of place have been modified and yet continue to be of vital importance in interpreting a world which travel and commerce have made very different from that of 1976. In his words: "sense of place has the potential to serve as a pragmatic foundation for addressing the profound local and global challenges, such as climate change and economic disparity, that are emerging in the present century".